Self-Actualization of the Main Characters in the Short Story of Filosofi Kopi by Dewi Lestari and its Implications in Literature Learning - Irmaida, Fadhia; Lustyantie, Ninuk; Yarmi, Gusti (Jurnal Paedagogy, 2023)
This study aims to increase students' knowledge of various extrinsic elements of literary works. In this case, the extrinsic element is the theory of basic needs by Abraham Maslow. Extrinsic elements must be analyzed to provide more content and benefits in literary works. The study was conducted at Vocational School 73 Jakarta, especially Class XI of Culinary Art, Hotel Accommodation, and Tourism Business Management programs. Each student was required to analyze a short story by Dewi Lestari's Filosofi Kopi. Students had the option of analyzing either the intrinsic or extrinsic elements. This study took a qualitative approach and was analyzed using descriptive qualitative techniques. The data source was an anthology of a short story entitled â€œFilosofi Kopiâ€ (Collection of Stories and Prose of a Decade) by Dewi Lestari, published by PT. Bentang Pustaka, eleventh edition, January 2015. Based on the analysis results in three classes, out of 104 students, 17 chose to analyze extrinsic elements; 12 understood extrinsic element analysis and the basic needs theory of Abraham Maslow; and five answered incorrectly. It means that students can understand Abraham Maslow's theory of humanistic psychology. Still, teachers need to pay more attention and provide direction on analyzing the extrinsic elements of literary works so that the students become more daring to analyze extrinsic elements of literary works.